Positive psychology in sport and physical activity an introduction - Brady, Abbe; Grenville-Cleave, Bridget (Routledge, 2018)
Positive psychology (PP) is a fast-developing area of research that emphasises personal growth and the positive qualities of life. This is the first book to apply the principles and practice of PP to sport and physical activity. With expert contributors from around the globe, real-life case studies, practical strategies and suggestions for future research in every chapter, this book is inspirational reading for all students, coaches, researchers and practitioners with an interest in sport and exercise psychology, mental health and well-being.